2006
DOI: 10.4141/s04-074
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil properties and 2,4-D sorption in a hummocky field as affected by landscape position and soil depth

Abstract: Gaultier, J., Farenhorst, A. and Crow, G. 2006. Spatial variability of soil properties and 2,4-D sorption in a hummocky field as affected by landscape position and soil depth. Can. J. Soil Sci. 86: 89-95. Since pesticide fate and leaching models increasingly incorporate spatial variability, the objective of this study was to quantify the variability of soil properties and 2,4-D sorption within a hummocky field as affected by landscape position and soil depth. Seventy-two soil cores collected at 5-m intervals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
5
25
1
Order By: Relevance
“…There was a positive linear relation between SOC and 2,4-D Kd, as observed for other surface and subsurface soils in agricultural fields (Farenhorst et al, 2003;Gaultier et al, 2006;Farenhorst et al, 2008). This is not surprising because soil organic carbon content is the primary factor influencing 2,4-D sorption (Reddy and Gambrell, 1987;Mallawatantri and Mulla, 1992;Hermosin and Cornejo, 1993;Johnson et al, 1995).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…There was a positive linear relation between SOC and 2,4-D Kd, as observed for other surface and subsurface soils in agricultural fields (Farenhorst et al, 2003;Gaultier et al, 2006;Farenhorst et al, 2008). This is not surprising because soil organic carbon content is the primary factor influencing 2,4-D sorption (Reddy and Gambrell, 1987;Mallawatantri and Mulla, 1992;Hermosin and Cornejo, 1993;Johnson et al, 1995).…”
Section: Discussionsupporting
confidence: 54%
“…In agreement with other studies (Hermosin and Cornejo, 1991), we also observed a negative linear relation between clay content and 2,4-D Kd. However, soil clay content had no significant influence on the sorption of 2,4-D in soil horizons of a conventional-tilled soil-landscape in Canada (Gaultier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides sorption, OC content has also been found to play a role in pesticide mineralization and microbial activity (Vinther et al 2008). Gaultier et al (2006) found that for the A horizon, regression models including only soil OC and carbonate content were sufficient to successfully predict 2,4-D sorption.…”
Section: Field-scale Variationmentioning
confidence: 99%